2012
DOI: 10.1111/j.1365-2133.2012.11049.x
|View full text |Cite
|
Sign up to set email alerts
|

Tandem repeated irritation in aged skin induces distinct barrier perturbation and cytokine profilein vivo

Abstract: Our results provide evidence for selective alterations in the cytokine profile and distinct barrier impairment kinetic following tandem repeated irritation with SLS and Tol in aged compared with young skin in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 45 publications
4
21
0
Order By: Relevance
“…While the concentrations of most mediators were increased in patch test reactions compared with their corresponding petrolatum controls, decreased values were found for several mediators, mainly those that are representatives of innate immunity, including IFN‐γ (MCI/MI), IL‐1α (chromium, MCI/MI, SLS), IL‐1β (nickel, SLS), IL‐7 (MCI/MI), IP‐10 (SLS) and IL‐1RA (SLS). IL‐1α levels in the SC have previously been shown to decrease after exposure to various skin irritants, which is in agreement with the effect of SLS found in the present study . The opposite, however, an increase of IL‐1α, has been found in the epidermis .…”
Section: Discussionsupporting
confidence: 92%
“…While the concentrations of most mediators were increased in patch test reactions compared with their corresponding petrolatum controls, decreased values were found for several mediators, mainly those that are representatives of innate immunity, including IFN‐γ (MCI/MI), IL‐1α (chromium, MCI/MI, SLS), IL‐1β (nickel, SLS), IL‐7 (MCI/MI), IP‐10 (SLS) and IL‐1RA (SLS). IL‐1α levels in the SC have previously been shown to decrease after exposure to various skin irritants, which is in agreement with the effect of SLS found in the present study . The opposite, however, an increase of IL‐1α, has been found in the epidermis .…”
Section: Discussionsupporting
confidence: 92%
“…[15][16][17][18][19] As TEWL is a measure of the barrier integrity, the lower baseline values in aged skin are suggestive of enhanced barrier function, unless dynamic stress tests revealing the underlying functional abnormalities have been performed. [20][21][22] Solvent treatment and tape stripping are validated and established experimental stress models for studying barrier integrity, impairment and repair kinetics in vivo. [23][24][25] Using both models, in the present study we showed functional improvement of the barrier parameters after exogenous acidification by topical application of a water-in-oil formulation with pH 4 in aged human skin.…”
Section: Discussionmentioning
confidence: 99%
“…Today, there are various skin measurements available for quantifying skin barrier function, skin appearance or skin mechanics . However, despite their importance, artificial stress or irritation tests provide much deeper insight into age‐related changes of skin function and biological capacity . For instance repeated tape stripping is widely applied to quantify the integrity of the stratum corneum.…”
Section: Discussionmentioning
confidence: 99%